Factors influencing outcomes in infants with seizure onset in first year of life: a single centre study - Anuar, Muhamad Azamin; Yahaya, Nor Azni; Zainal Abidin, Muhammad 'Adil; Tan, Soo Hong; Yeap, Cai Fong (2022)
Epilepsy has a high incidence in the first year of life and its course is highly variable. There are limited study on infantile onset epilepsy, excluding infantile spasms, in terms of prognostic factors in outcome measures. Therefore, we aimed to describe the seizure control, developmental outcome and prognostic factor in a single centre study. Methods: Data of patients with seizure onset before the age of 12 months and followed up more than 2 years, were retrieved from electronic patient records of Hospital Raja Perempuan Zainab II. The patients’ records were retrospectively reviewed and clinical outcomes were assessed based on the last follow-up. Results: Of the 75 patients, 60 (80%) have seizure good seizure control or entered remission. Twenty-five (33.3%) were found to have developmental delay at the last follow-up and 17/32 (53.1%) have abnormal neuro-radiological findings. Onset of seizures before 8 months old, present of delay development at presentation and abnormal radiological findings were likely associated with poor seizure control (p<0.05). Conclusions: This study demonstrated that most patient with infantile epilepsy can achieve seizure remission. There are factors that contributed to poor seizure control and associated with developmental delay. Infantile onset epilepsies might require extensive resources and precision intervention for better outcome.